Effect of Extra Curricular Activity on Student’s Academic Performance - Ahmad, Mushtaq; Rahman, Md Fashiur; Ali, Mohammad; Rahman, Farial Naima; Al Azad, Md Abdus Samad (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Extracurricular activities are part and parcel of modern day’s academic curriculum. It provides them a positive character building opportunity and teaches ways to develop discipline, commitment, tenacity, self control and a healthy respect for college authority. Objectives: To find out the relation between student’s participation in extracurricular activities in college campus and academic performance. Materials and Methods: This cross sectional study was conducted at Armed Forces Medical College, Dhaka from February 2015 to October 2015. A total of 475 students belonged to four different phase groups were selected as research sample. The dependant variable was fixed at overall improvement in examination results where as independent variables were gender, participation and non participation in all extra academic activities performed at college campus. Research Data were collected from records of training section of the college. Data was analyzed in terms of percentage and Pearson Chi-Square test using SPSS-20 version of software. Results: Total participant students were 475 and Male female student ratio was 168(35.36%): 307 (64.64%). In outdoor games and sports, males showed better participation than female 121(72.02%): 89(28.99%). But the number of participating female increased in case of indoor games {male 115(68.45%): female 205(66.77%)}. Considering photography club participation male showed better response {male 76(45.23%): female 41(13.35%)}. In case of cultural and debate club activities females showed greater response {female 226(73.61%): male 106(63.09%)}. In medical carnival club activities female: male score was almost similar {Female 207(67.43%): male 112(66.66%)}. The class attendance (more than 75%) of participating students {male 106(94.64%) and female 208 (92.04%)) were much better than non participating students. Regarding result of term finals all the participants showed better academic performance {male 87(77.68%) and female 187 (82.74%)}. In Professional MBBS examinations participant 103 (91.96%) male and 201 (88.94%) female passed at one chance while percentage of pass was less in non participant students {31 (55.35%) male and 44 (57.14%) female}. Pearson Chi-Square test result showed significance in all the above aspects. Conclusion: Students participating in extracurricular activities generally benefit from having better examination results, higher self concept, higher standardized test scores and educational attainment. Students often learned skills such as teamwork and leadership from college club activities while decreasing the likelihood of different problem behaviors. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 41-46